Analisis Faktor Efektivitas Iklan Pada Putusan Pembelian : (Studi Kasus Pemakai Sepeda Motor Matic Di Indrapura) - Nainggolan, Pinondang; Napitupulu, Resna; Manik, Sriyhardiyanti (Sekolah Tinggi Ilmu Ekonomi Bina karya, 2022)
The aim of the research is to analyze the effectiveness of advertising on automatic motorbike purchases made at PT. Abiwara III Work Award, Indrapura. Data collection techniques using a questionnaire. The population is automatic motorbike users in Indrapura as many as 365 people with the Random Sampling technique, and the sampling uses the Arikunto formula. The number of samples is 73 people. Research with multiple linear regression analysis using SPSS 25. The research results illustrate: The quality of advertising messages has no impact on purchasing decisions. D. The attractiveness of advertising has no effect on purchasing decisions. The frequency of ad serving has an effect on purchasing decisions. The most dominant factor is the frequency of ad serving. The higher the Ad Show Frequency level, the more popular it will be in society to remember the information conveyed in the promotion of Honda motorcycles